Programmable logic devices e-course - Shulgina, Yu. V. specialist in the field of electronics engineer Tomsk Polytechnic University 1987- (TPU Moodle, 2016)
Build an effective FPGA design using synchronous design techniques, instantiate appropriate device resources, use proper HDL coding techniques, make good pin assignments, set basic timing constraints, and use the Quartus II to build, synthesize, implement, and download a design.